Low-temperature fast-charging type lithium ion battery
By designing a multi-layer structure negative electrode in a lithium-ion battery and using a low-temperature electrolyte, the problems of low charging and discharging efficiency and lithium precipitation of lithium-ion batteries in a low-temperature environment are solved, and efficient 1C charging and discharging at -40℃ are achieved and high capacity retention rate for long cycles.
Patent Information
- Application Number
- CN202411631196.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
Existing lithium-ion batteries have low charge and discharge efficiency in low temperature environments, and are prone to lithium precipitation, resulting in capacity attenuation and battery failure, especially in extreme low temperature environments in northern regions.
By designing the negative electrode of a multi-layer structure, including a copper foil layer, a lithium titanate layer, a conductive carbon black layer and a graphite composite hard carbon layer, and using a low-temperature electrolyte, the embeddedness of lithium ions and the low-temperature performance of the battery are improved.
Achieve efficient operation of lithium-ion batteries at -40℃, with a capacity retention rate exceeding 70% of the 1C charge and discharge capacity of normal temperature, and during the 500-week 1C charge and discharge cycle of low temperature -40℃, the capacity retention rate still exceeds the initial 70% of the low-temperature discharge capacity.
Smart Images

Figure CN119447420A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium ion battery, in particular to a low-temperature fast-charging lithium ion battery, belonging to the technical field of batteries. Background Art
[0002] Lithium-ion batteries have significant advantages such as high energy density, long service life, high operating voltage, long cycle life, and no memory effect. They are widely used in smart phones, laptops, smart wearable devices, energy storage batteries, electric vehicles and other equipment. Especially in the field of electric vehicles, the development of lithium batteries is very rapid. However, since lithium-ion batteries, a chemical power source, are sensitive to ambient temperature, their discharge efficiency decreases significantly when they are at -20°C or even lower. In addition, traditional lithium batteries with graphite as the negative electrode of lithium-ion batteries are easily charged at temperatures below 0°C, which can easily lead to lithium precipitation on the negative electrode surface, capacity decay, battery expansion, and eventually rapid failure, and even cause combustion accidents.
[0003] In recent years, as the proportion of lithium battery-powered electric vehicles in the market has increased year by year, the purchase rate of pure electric vehicles in the southern market has been significantly higher than that in the northern market. The reason for this is that the lithium battery packs used in pure electric vehicles cannot support the low temperature environment in the north after winter. For example, in Northeast China and the Qinghai-Tibet Plateau, the extreme low temperature in winter can be as low as minus 40 degrees Celsius, and some areas are close to the limit of minus 50 degrees Celsius. This puts higher requirements on the performance of electric vehicles. Traditional coping strategies such as preheating batteries and oil circuits can barely cope with it, but they are inefficient, time-consuming, and consume a lot of resources, and are difficult to meet. To meet customer needs, the lithium-ion batteries that can support low-temperature charging and discharging on the market are mainly lithium titanate lithium-ion batteries. However, due to the high voltage platform of lithium titanate and the specific capacity of only about 170mAh / g, which is half of that of graphite, the energy density of lithium-ion batteries with pure lithium titanate as the negative electrode is less than 100Wh / kg. From the perspective of battery life, it is very easy to cause customer mileage anxiety. Therefore, it is urgent and important to develop a low-temperature lithium-ion battery that supports temperature environments below -20°C, 1C~3C fast charging, and energy density >190Wh / kg to open up the northern electric vehicle market. Summary of the invention
[0004] In order to solve the technical problems of low low-temperature charging and discharging efficiency and lithium deposition during low-temperature charging in existing lithium batteries, the purpose of the present invention is to provide a low-temperature fast-charging lithium-ion battery, which solves the technical problems of low-temperature charging and lithium deposition and low efficiency of lithium-ion batteries by improving the negative electrode structure and adopting a low-temperature electrolyte.
[0005] In order to achieve the above technical objectives, the present invention provides a low-temperature fast-charging lithium-ion battery, including a positive electrode, a negative electrode, an electrolyte, a diaphragm and a casing. The negative electrode has a multi-layer structure, with a copper foil layer in the middle, and lithium titanate layers, conductive carbon black layers and graphite composite hard carbon layers on both sides of the copper foil layer in sequence; the positive electrode includes a lithium cobalt oxide system, a ternary system or other composite systems; the electrolyte is a low-temperature electrolyte.
[0006] The key to the low-temperature fast-charging lithium-ion battery of the present invention is the design of a negative electrode with a special multilayer structure, specifically, both sides of the copper foil current collector are respectively lithium titanate layer, conductive carbon black layer and graphite composite hard carbon layer. From the perspective of lithium embedding dynamics, the lithium titanate layer on the bottom layer of the copper foil current collector surface can ensure that lithium ions can be smoothly embedded in the lithium titanate layer during high current charging under low temperature environment. Its higher lithium embedding potential effectively avoids the lithium precipitation phenomenon caused by the lithium precipitation potential caused by polarization being higher than the lithium embedding potential. The conductive coating in the middle can effectively improve the interface contact between the lithium titanate layer and the graphite composite hard carbon layer, and improve electronic conduction at the same time. The graphite composite hard carbon layer used in the outer layer is the key to high specific energy. Since the first charge and discharge efficiency of hard carbon is low, the energy density of the battery will be reduced. However, the low-temperature charge and discharge performance of hard carbon is relatively good. Graphite has a high capacity and a high first coulomb efficiency, but poor low-temperature charging performance. Therefore, combining the advantages of the two and utilizing graphite composite hard carbon, both the low-temperature capability of the negative electrode is improved and the influence of low first efficiency on energy density is reduced. The multi-layer structure negative electrode combined with the low-temperature electrolyte can achieve lithium-ion battery 1C discharge to 2.0V at low temperature of -40℃, with a capacity retention rate of more than 70% of the 1C discharge capacity at normal temperature, and 1C charge to 4.3V at low temperature of -40℃, with a capacity retention rate of more than 60% of the 1C charging capacity at normal temperature, and 500 cycles of 1C charge and discharge at low temperature of -40℃, with a capacity retention rate of more than 70% of the initial low-temperature discharge capacity.
[0007] As a preferred solution, the thickness of the lithium titanate layer is 5-20 μm.
[0008] As a preferred solution, the thickness of the conductive carbon black layer is 1-3 μm.
[0009] As a preferred solution, the thickness of the hard carbon composite graphite layer is 50-120 μm.
[0010] The negative electrode of the present invention has a multi-layer structure, and the synergistic effect between the various layer structures contributes significantly to the energy density of the negative electrode. The lithium titanate layer on the surface of the copper foil dominates the transmission of lithium ions at low temperatures and plays a dominant role in the migration speed of lithium ions. However, since the electronic conductivity of the lithium titanate layer is relatively poor, it is not conducive to the transmission of electrons between the lithium titanate and the graphite layer. Therefore, the middle conductive carbon black layer mainly plays a role in accelerating electron transfer and reducing ohmic impedance. The outermost hard carbon composite graphite layer is the main contributor to the lithium storage capacity. The hard carbon composite graphite layer is used to increase the overall specific capacity of the negative electrode, thereby increasing the energy density.
[0011] As a preferred solution, the lithium titanate layer contains lithium titanate, carbon nanotubes and superconducting carbon black, wherein the mass content of lithium titanate is 90% to 96%, the mass content of carbon nanotubes is 0.1% to 3%, and the mass content of superconducting carbon black is 0.1% to 2%. The lithium titanate layer also contains components such as a binder, such as polyvinylidene fluoride PVDF, with a mass content of 1% to 5%. The linear carbon nanotubes are introduced to play a conductive connection role, while the granular carbon black plays a filling role. The two cooperate to build a good conductive network, which mainly plays a role in electron transmission and reduces the internal resistance and polarization of the lithium titanate component.
[0012] As a preferred solution, the conductive carbon black layer contains conductive carbon black, wherein the mass content of the conductive carbon black is 94% to 98%. The conductive carbon black layer also contains components such as a binder, such as styrene-butadiene rubber (SBR).
[0013] As a preferred solution, the graphite composite hard carbon layer contains artificial graphite, hard carbon and carbon nanotubes, wherein the mass content of graphite is 65% to 85%, the mass content of hard carbon is 10% to 30%, and the mass content of carbon nanotubes is 0.1% to 2%. The graphite composite hard carbon layer also contains a binder, such as LA133, which accounts for 2% to 4% of the mass of the graphite composite hard carbon layer. Graphite and hard carbon in the graphite composite hard carbon layer mainly play the role of lithium storage. Graphite has a high specific capacity for lithium storage and a high initial charge and discharge efficiency, but has a low lithium insertion potential, which is not conducive to low-temperature charging. Although hard carbon has a high specific capacity and good low-temperature charging performance, it has a low initial charge and discharge, which will lead to a decrease in the overall energy density of the battery. Therefore, the advantages of graphite and hard carbon are taken separately, with graphite as the main component and part of the hard carbon as the composite component, which can improve the low-temperature charging effect while ensuring that the specific energy is not damaged. Carbon nanotubes mainly play the role of improving electron transfer, and LA133 mainly plays the role of bonding.
[0014] As a preferred solution, the low-temperature electrolyte includes a solvent, a lithium salt and a functional additive.
[0015] As a preferred solution, the solvent comprises a combination of at least two of a carboxylate solvent, a carbonate solvent, and a nitrile solvent. The freezing point and boiling point temperature range of the combined solvent are widened relative to a single solvent, and the combination of different solvents can optimize indicators such as dielectric constant and viscosity, as well as positive and negative electrode film formation. The freezing point of carbonate is relatively high, which is not conducive to the conductivity of the electrolyte at low temperatures, but carbonate has stable electrochemical properties and high oxidation potential. At the same time, EC and the like can also participate in film formation, which is beneficial to the stability of the battery's electrical performance. The introduction of carboxylate and nitrile solvents can greatly improve the conductivity of the electrolyte at low temperatures and reduce the low-temperature polarization impedance.
[0016] As a preferred solution, the functional additive includes fluorinated ethylene carbonate, vinylene carbonate, vinylene sulfate and trimethylsilyl difluoroacetate. By introducing trimethylsilyl difluoroacetate into the functional additive of the present invention, the voltage platform during low-temperature discharge can be increased, the polarization impedance at low temperature can be reduced, and the low-temperature operation of the lithium-ion battery can be provided with a basis. In addition, fluorinated ethylene carbonate, vinylene carbonate and vinylene sulfate are all film-forming additives, and the formation of a dense and thin SEI film can reduce the polarization impedance, which is beneficial to low-temperature charging and discharging.
[0017] As a preferred solution, the lithium salt includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate and lithium difluorooxalatoborate. The composite salt has a relatively high solubility at low temperatures, effectively guarantees the conductivity at low temperatures, and improves the discharge platform voltage.
[0018] As a preferred solution, the carboxylate solvent includes at least one of ethyl propionate and propyl propionate;
[0019] As a preferred solution, the carbonate solvent includes at least one of propylene carbonate, ethyl methyl carbonate and diethyl carbonate.
[0020] As a preferred solution, the nitrile solvent includes at least one of n-valeronitrile and fluorobutyronitrile.
[0021] As a preferred solution, the solvent comprises the following mass percentage components: 40% to 70% carboxylate solvents, 15% to 45% carbonate solvents, and 5% to 15% nitrile solvents. Carboxylates have a low freezing point, but also a low boiling point, and are prone to vaporization at high temperatures above 65°C, affecting the use of the battery. Carbonates have a high freezing point, a high boiling point, and relatively poor low-temperature performance. By using carboxylates as the main solvent and carbonates as the auxiliary solvent, the wide temperature performance of the battery can be improved. Nitrile solvents have a lower freezing point and a higher dielectric constant, which has a better effect on the transmission of lithium ions, especially at low temperatures, but their flash point is low and can easily cause safety accidents. Therefore, they are added as auxiliary solvents.
[0022] As a preferred solution, the mass proportion of each component in the functional additive in the low-temperature electrolyte is: 1% to 10% of fluorinated vinyl carbonate, 0.3% to 1.5% of vinylene carbonate, 1% to 2% of vinylene sulfate, and 0.5% to 3% of trimethylsilyl difluoroacetate. Since fluorinated vinyl carbonate and vinylene sulfate have low film-forming potentials, high film-forming priority, and are beneficial to low-temperature performance, but vinylene sulfate is prone to gas production, they are used as secondary film-forming additives, and vinylene carbonate and trimethylsilyl difluoroacetate are used as auxiliary additives, mainly to stabilize the positive and negative electrode interfaces during fast charging of the battery.
[0023] As a preferred solution, the mass proportion of each component in the lithium salt in the low-temperature electrolyte is: lithium hexafluorophosphate 10%~18%, lithium bisfluorosulfonyl imide 1%~6%, lithium difluorophosphate 0.2~1%, lithium difluorooxalate borate 0.5%~2%. As the main salt, lithium hexafluorophosphate has high solubility, good stability, and relatively comprehensive high and low temperature performance. Lithium bisfluorosulfonyl imide has better solubility, conductivity and wide temperature performance, but it is easy to corrode aluminum foil, so its dosage is controlled. As the secondary salt of lithium hexafluorophosphate, lithium difluorophosphate and lithium difluorooxalate borate mainly play the role of optimizing the film formation at the positive and negative electrode interfaces.
[0024] As a preferred solution, the housing is an aluminum-plastic film soft package structure or a square aluminum shell structure.
[0025] As a preferred solution, the separator is arranged in a Z-shape between the positive electrode and the negative electrode.
[0026] The negative electrode of the present invention is prepared by the following method: firstly, a lithium titanate layer is coated on the copper foil, and the thickness of the lithium titanate layer is 5-20 μm; then, a conductive carbon black layer is coated on the lithium titanate layer, and the thickness of the conductive carbon black layer is 1-3 μm; finally, a graphite composite hard carbon layer is coated on the conductive carbon black layer, and the thickness of the graphite composite hard carbon layer is 50-120 μm. The slurry used for coating the lithium titanate layer is formed by mixing lithium titanate, carbon nanotubes, superconducting carbon black and a binder in an aqueous solution, wherein the mass proportion of lithium titanate is 90%-96%, the mass proportion of carbon nanotubes is 0.1%-3%, the mass proportion of superconducting carbon black is 0.1%-2%, and the mass proportion of the binder is 1%-5%. The slurry used for coating the conductive carbon black layer is formed by mixing conductive carbon black, dispersant and binder in aqueous solution, wherein the mass proportion of conductive carbon black is 94%~98%, the mass proportion of dispersant is 0.2%~2%, and the mass proportion of binder is 1.5%~4%. The particles of conductive carbon black are nanometer-scale. In order to prevent the agglomeration of materials, sodium carboxymethyl cellulose and polyamine alcohol surfactants need to be added as dispersants for effective dispersion. The binder mainly plays a bonding role. The slurry used for coating the graphite composite hard carbon layer is formed by mixing artificial graphite, hard carbon, carbon nanotubes, and binder in aqueous solution, wherein the mass proportion of graphite is 65%~85%, the mass proportion of hard carbon is 10%~30%, the mass proportion of carbon nanotubes is 0.1%~2%, and the mass proportion of binder is 2%~4%.
[0027] Compared with the prior art, the technical effects brought by the technical solution of the present invention are as follows:
[0028] The energy density of the low-temperature fast-charging lithium-ion battery provided by the present invention is higher than 190Wh / kg, and supports 1C charging and discharging at -40°C; more specifically, the lithium-ion battery can be discharged to 2.0V at 1C at a low temperature of -40°C, with a capacity retention rate greater than 70% of the 1C discharge capacity at normal temperature, and charged to 4.3V at 1C at a low temperature of -40°C, with a capacity retention rate greater than 60% of the 1C charging capacity at normal temperature, and the low-temperature 1C charge and discharge cycle of -40°C for 500 weeks has a capacity retention rate greater than 70% of the initial low-temperature discharge capacity.
[0029] The low-temperature fast-charging lithium-ion battery provided by the present invention has a simple structural design, is easy to prepare, has low cost, and is conducive to popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the structure of the multilayer negative electrode of the lithium ion battery of Example 1; wherein 1 is a graphite composite hard carbon layer, 2 is a conductive carbon black layer, 3 is a lithium titanate layer, and 4 is a copper foil layer.
[0031] Figure 2Schematic diagram of the discharge of the lithium-ion battery of Example 1 at different temperatures; it can be seen from the figure that the battery can still discharge more than 60% of the power when discharged to 2.0V at -40℃ 0.2C.
[0032] Figure 3 This is a comparison chart of the charge and discharge cycle of the lithium-ion battery of Example 1 under low temperature (-40°C) 1C conditions and the low temperature (-40°C) cycle of a conventional lithium battery; it can be seen from the figure that the battery still has a capacity retention rate of more than 92% of the initial low temperature discharge capacity after 300 cycles of charge and discharge at -40°C 1C, while the capacity of the conventional low temperature battery in comparison is severely attenuated under low temperature -40°C cycles.
[0033] Figure 4 This is a SEM image of the negative electrode interface of the lithium battery of Example 1 after low-temperature cycling. DETAILED DESCRIPTION
[0034] The content of the present invention is further described in detail below in conjunction with specific embodiments and drawings, but the specific embodiments of the present invention are not limited to the following specific embodiments.
[0035] Example 1
[0036] The low-temperature fast-charging lithium-ion battery described in this embodiment takes the 1090155-20Ah battery as an example, and its battery composition is as follows:
[0037] For the positive electrode, the formula of the positive electrode slurry is LiCoO2 lithium cobalt oxide accounting for 96.5% by weight, carbon nanotubes accounting for 0.3% by weight, VGCF accounting for 0.2% by weight, conductive carbon black Super P accounting for 1.5% by weight, and binder PVDF accounting for 1.5% by weight; the positive electrode is coated on a 12μm aluminum foil by a coating machine, with a single-sided surface density of 13mg / cm 2 , thickness 87μm.
[0038] For the negative electrode part, the electrode slurry used for the lithium titanate layer of the negative electrode is prepared by mixing lithium titanate, carbon nanotubes, superconducting carbon black and a binder in an aqueous solution, with a mass ratio of 95.5% for lithium titanate, 1.5% for carbon nanotubes, 0.2% for superconducting carbon black, 1.2% for CMC and 1.6% for SBR; the slurry used for the conductive carbon black layer is prepared by mixing conductive carbon black, a dispersant and a binder in an aqueous solution, with a mass ratio of 97.5% for conductive carbon black, 0.5% for polyamino alcohol, 0.5% for CMC and 1.5% for SBR; the slurry used for the graphite composite hard carbon layer is prepared by mixing artificial graphite, hard carbon, carbon nanotubes and a binder in an aqueous solution, with a mass ratio of 78% for graphite, 17% for hard carbon, 0.6% for carbon nanotubes, 1% for conductive carbon black and 3.4% for LA133 as the binder. The lithium titanate is first coated on an 8μm thick copper foil by a coating machine with a coating thickness of 20μm, and then the coated substrate is transferred to a gravure printing plate to coat a conductive carbon black layer with a coating thickness of 2μm, and finally transferred to a coating machine to coat a graphite composite hard carbon layer with a coating thickness of 90μm.
[0039] The positive and negative electrodes are punched out using a punching machine, and the positive and negative electrodes and separators are stacked in 48 layers in the order of separator-negative electrode-separator-positive electrode-separator. The pole ears are then welded and packaged using a formed aluminum-plastic film, which is then baked and injected with liquid. The assembly procedure can refer to the soft-pack lithium-ion battery assembly process.
[0040] The solvent of the low-temperature electrolyte is composed of ethyl propionate, propylene carbonate, ethyl methyl carbonate and fluorobutyronitrile, wherein the proportion of ethyl propionate is 50% by mass, the proportion of propylene carbonate is 18% by mass, the proportion of ethyl methyl carbonate is 25% by mass, and the proportion of fluorobutyronitrile is 7% by mass; the additives include fluorinated vinyl carbonate, vinylene carbonate, vinylene sulfate, and trimethylsilyl difluoroacetate, wherein fluorinated vinyl carbonate accounts for 4% by mass of the whole electrolyte, and .... Vinylene ester accounts for 0.5% of the total electrolyte mass ratio, vinylene sulfate accounts for 2% of the total electrolyte mass ratio, and trimethylsilyl difluoroacetate accounts for 0.5% of the total electrolyte mass ratio; lithium salts include lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium difluorophosphate, and lithium difluorooxalate borate, among which lithium hexafluorophosphate accounts for 16% of the total electrolyte mass ratio, lithium bisfluorosulfonyl imide accounts for 2% of the total electrolyte mass ratio, lithium difluorophosphate accounts for 0.7% of the total electrolyte mass ratio, and lithium difluorooxalate borate accounts for 1% of the total electrolyte mass ratio.
[0041] The prepared battery has a capacity of 20Ah and an energy density of 200Wh / kg.
[0042] Example 2
[0043] The low-temperature fast-charge lithium-ion battery described in this embodiment takes the 6060110-5Ah battery as an example, and its battery composition is as follows:
[0044] For the positive electrode, the formula of the positive electrode slurry is LiNi 0.6 Co 0.2 Mn 0.2 O2 ternary materials account for 95.3% by mass, carbon nanotubes account for 0.5% by mass, Ketjen black accounts for 0.2% by mass, conductive carbon black Super P accounts for 2.5% by mass, and binder PVDF accounts for 1.5%; the positive electrode is coated on 12μm aluminum foil by a coating machine, with a single-sided surface density of 13mg / cm 2 , thickness 87μm.
[0045] For the negative electrode part, the electrode slurry used for the lithium titanate layer of the negative electrode is prepared by mixing lithium titanate, carbon nanotubes, superconducting carbon black and a binder in an aqueous solution, with a mass ratio of 95.5% for lithium titanate, 0.5% for carbon nanotubes, 0.2% for superconducting carbon black and 3.8% for PVDF; the slurry used for the conductive carbon black layer is prepared by mixing conductive carbon black, a dispersant and a binder in an aqueous solution, with a mass ratio of 96.5% for conductive carbon black, 0.5% for polyamino alcohol, 1% for CMC and 2% for SBR; the slurry used for the graphite composite hard carbon layer is prepared by mixing artificial graphite, hard carbon, carbon nanotubes and a binder in an aqueous solution, with a mass ratio of 84% for graphite, 10% for hard carbon, 0.5% for carbon nanotubes, 2% for conductive carbon black and 3.5% for LA133 as the binder. The lithium titanate is first coated on an 8μm thick copper foil by a coater with a coating thickness of 15μm, and then the coated substrate is transferred to a gravure printing plate to coat a conductive carbon black layer with a coating thickness of 2μm, and finally transferred to a coater to coat a graphite composite hard carbon layer with a coating thickness of 100μm.
[0046] The positive and negative electrodes are punched out using a punching machine, and the positive and negative electrodes and separators are stacked in 25 layers in the order of separator-negative electrode-separator-positive electrode-separator. The pole ears are then welded and packaged using a formed aluminum-plastic film, which is then baked and injected with liquid. The assembly procedure can refer to the soft-pack lithium-ion battery assembly process.
[0047] The solvent of the low-temperature electrolyte is composed of ethyl propionate, propylene carbonate, ethyl methyl carbonate and fluorobutyronitrile, wherein the proportion of ethyl propionate is 50% by mass, the proportion of propylene carbonate is 18% by mass, the proportion of ethyl methyl carbonate is 25% by mass, and the proportion of fluorobutyronitrile is 7% by mass; the additives include fluorinated vinyl carbonate, vinylene carbonate, vinylene sulfate, and trimethylsilyl difluoroacetate, wherein fluorinated vinyl carbonate accounts for 4% by mass of the whole electrolyte, and .... Vinylene ester accounts for 0.5% of the total electrolyte mass ratio, vinylene sulfate accounts for 2% of the total electrolyte mass ratio, and trimethylsilyl difluoroacetate accounts for 0.5% of the total electrolyte mass ratio; lithium salts include lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium difluorophosphate, and lithium difluorooxalate borate, among which lithium hexafluorophosphate accounts for 16% of the total electrolyte mass ratio, lithium bisfluorosulfonyl imide accounts for 2% of the total electrolyte mass ratio, lithium difluorophosphate accounts for 0.7% of the total electrolyte mass ratio, and lithium difluorooxalate borate accounts for 1% of the total electrolyte mass ratio.
[0048] The prepared battery has a capacity of 5Ah and an energy density of 210Wh / kg.
[0049] Example 3
[0050] The low-temperature fast-charge lithium-ion battery described in this embodiment takes the 6060110-5Ah battery as an example, and its battery composition is as follows:
[0051] For the positive electrode, the formula of the positive electrode slurry is LiNi 0.6 Co 0.2 Mn 0.2 O2 ternary materials account for 95.3% by mass, carbon nanotubes account for 0.5% by mass, Ketjen black accounts for 0.2% by mass, conductive carbon black Super P accounts for 2.5% by mass, and binder PVDF accounts for 1.5%; the positive electrode is coated on 12μm aluminum foil by a coating machine, with a single-sided surface density of 13mg / cm 2 , thickness 80μm.
[0052] For the negative electrode part, the electrode slurry used for the lithium titanate layer of the negative electrode is prepared by mixing lithium titanate, carbon nanotubes, superconducting carbon black and a binder in an aqueous solution, with a mass ratio of 95.5% for lithium titanate, 0.5% for carbon nanotubes, 2.0% for SP and 2.0% for PVDF; the slurry used for the conductive carbon black layer is prepared by mixing conductive carbon black, a dispersant and a binder in an aqueous solution, with a mass ratio of 96.5% for conductive carbon black, 0.5% for polyamino alcohol, 1% for CMC and 2% for SBR; the slurry used for the graphite composite hard carbon layer is prepared by mixing artificial graphite, hard carbon, carbon nanotubes and a binder in an aqueous solution, with a mass ratio of 84% for graphite, 10% for hard carbon, 0.5% for carbon nanotubes, 2% for conductive carbon black and LA133 as the binder with a mass ratio of 3.5%. The lithium titanate is first coated on an 8μm thick copper foil by a coater with a coating thickness of 5μm, and then the coated substrate is transferred to a gravure printing plate to coat a conductive carbon black layer with a coating thickness of 2μm, and finally transferred to a coater to coat a graphite composite hard carbon layer with a coating thickness of 80μm.
[0053] The positive and negative electrodes are punched out using a punching machine, and the positive and negative electrodes and separators are stacked in 25 layers in the order of separator-negative electrode-separator-positive electrode-separator. The pole ears are then welded and packaged using a formed aluminum-plastic film, which is then baked and injected with liquid. The assembly procedure can refer to the soft-pack lithium-ion battery assembly process.
[0054] The solvent of the low-temperature electrolyte is composed of ethyl propionate, propylene carbonate, ethyl methyl carbonate and fluorobutyronitrile, wherein the proportion of ethyl propionate is 50% by mass, the proportion of propylene carbonate is 18% by mass, the proportion of ethyl methyl carbonate is 25% by mass, and the proportion of fluorobutyronitrile is 7% by mass; the additives include fluorinated vinyl carbonate, vinylene carbonate, vinylene sulfate, and trimethylsilyl difluoroacetate, wherein fluorinated vinyl carbonate accounts for 4% by mass of the whole electrolyte, and .... Vinylene ester accounts for 0.5% of the total electrolyte mass ratio, vinylene sulfate accounts for 2% of the total electrolyte mass ratio, and trimethylsilyl difluoroacetate accounts for 0.5% of the total electrolyte mass ratio; lithium salts include lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium difluorophosphate, and lithium difluorooxalate borate, among which lithium hexafluorophosphate accounts for 16% of the total electrolyte mass ratio, lithium bisfluorosulfonyl imide accounts for 2% of the total electrolyte mass ratio, lithium difluorophosphate accounts for 0.7% of the total electrolyte mass ratio, and lithium difluorooxalate borate accounts for 1% of the total electrolyte mass ratio.
[0055] The prepared battery has a capacity of 5Ah and an energy density of 215Wh / kg.
Claims
1. A low-temperature fast-charge lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, a diaphragm and a housing, characterized in that: The negative electrode has a multi-layer structure, wherein the middle is a copper foil layer, and both sides of the copper foil layer are sequentially provided with a lithium titanate layer, a conductive carbon black layer and a graphite composite hard carbon layer; The positive electrode includes a lithium cobalt oxide system, a ternary system or other composite systems; The electrolyte is a low-temperature electrolyte.
2. A low-temperature fast-charge lithium-ion battery according to claim 1, characterized in that: The thickness of the lithium titanate layer is 5-20 μm; The thickness of the conductive carbon black layer is 1-3 μm; The thickness of the conductive carbon black layer is 50-120 μm.
3. A low-temperature fast-charge lithium-ion battery according to claim 1 or 2, characterized in that: The lithium titanate layer contains lithium titanate, carbon nanotubes and superconducting carbon black, wherein the mass content of lithium titanate is 90% to 96%, the mass content of carbon nanotubes is 0.1% to 3%, and the mass content of superconducting carbon black is 0.1% to 2%; The conductive carbon black layer contains conductive carbon black, wherein the mass content of the conductive carbon black is 94% to 98%; The graphite composite hard carbon layer comprises artificial graphite, hard carbon and carbon nanotubes, wherein the mass content of graphite is 65% to 85%, the mass content of hard carbon is 10% to 30%, and the mass content of carbon nanotubes is 0.1% to 2%.
4. A low-temperature fast-charge lithium-ion battery according to claim 1, characterized in that: The low-temperature electrolyte comprises a solvent, a lithium salt and a functional additive.
5. A low-temperature fast-charge lithium-ion battery according to claim 4, characterized in that: The solvent comprises a combination of at least two of a carboxylate solvent, a carbonate solvent and a nitrile solvent; The functional additives include fluorinated vinyl carbonate, vinylene carbonate, vinylene sulfate and trimethylsilyl difluoroacetate; The lithium salts include lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate and lithium difluorooxalatoborate.
6. A low-temperature fast-charge lithium-ion battery according to claim 5, characterized in that: The carboxylate solvent includes at least one of ethyl propionate and propyl propionate; The carbonate solvent includes at least one of propylene carbonate, ethyl methyl carbonate and diethyl carbonate; The nitrile solvent includes at least one of n-valeronitrile and fluorobutyronitrile.
7. A low-temperature fast-charge lithium-ion battery according to claim 4, 5 or 6, characterized in that: The solvent comprises the following components in percentage by weight: 40% to 70% of a carboxylate solvent, 15% to 45% of a carbonate solvent, and 5% to 15% of a nitrile solvent.
8. A low-temperature fast-charge lithium-ion battery according to claim 4 or 5, characterized in that: The mass proportion of each component in the functional additive in the low-temperature electrolyte is: 1% to 10% of fluorinated vinyl carbonate, 0.3% to 1.5% of vinylene carbonate, 1% to 2% of vinylene sulfate, and 0.5% to 3% of trimethylsilyl difluoroacetate; The mass proportions of the components of the lithium salt in the low-temperature electrolyte are: lithium hexafluorophosphate 10%~18%, lithium bis(fluorosulfonyl)imide 1%~6%, lithium difluorophosphate 0.2%~1%, and lithium difluorooxalatoborate 0.5%~2%.
9. A low-temperature fast-charge lithium-ion battery according to claim 1, characterized in that: The shell is an aluminum-plastic film soft package structure or a square aluminum shell structure; The separator is Z-shaped and arranged between the positive electrode and the negative electrode.